Hospital Management Strategies in Erythropoiesis-Stimulating Agents Therapy for Chronic Kidney Disease: A Systematic Literature Review - Akhmad Ulil Albab; Aflit Nuryulia Praswati; Yuli Kusumawati; Eko Sugihanto (MEDICA (International Medical Scientific Journal), 2026)
Anemia is a severe and costly complication in patients with end-stage Chronic Kidney Disease (CKD) undergoing long-term maintenance hemodialysis. The management of Erythropoiesis-Stimulating Agents (ESAs) therapy frequently faces challenges due to patient variability, dose inertia, and the lack of standardized managerial oversight. This study aims to analyze the strategic role of hospital management in implementing Clinical Practice Guidelines (CPGs) and Standard Operating Procedures (SOPs), evaluating their impact on clinical stability and economic outcomes. The method used is a Systematic Literature Review (SLR) of 21 scientific articles from Scopus, PubMed, and Google Scholar databases published between 2020 and 2025. Study quality, evidence heterogenity, and risk of bias were critically appraised by prioritizing methodological rigor and alignment with clinical implementation. The review results indicate that structured ESA protocols managed by specialist healthcare professionals, such as pharmacists or clinical nurse specialists, exhibit clinical effectiveness equivalent to conventional physician-led care while improving operational efficiency. The implementation of these protocols significantly lowers drug dosages, with studies showing a median weekly ESA dose reduction of up to 34% compared to discretionary care. Furthermore, achieving a high Hemoglobin Time-in-Range (TiR ≥60% within 10.0–11.5 g/dL) strongly correlates with a 19% decline in hospitalization rates and a 43% reduction in blood transfusion requirements. Economically, protocol-driven management demonstrates potential for substantial value; however, exact financial outcome should be interpretedwith caution due to the heterogenity of regional healthcare financing systems. With specific settings, proactive models reported annualized total healthcare cost savings reaching $33,921 per patient, including $6,201 in reduced transfusion costs. The novelty of this research lies in highlighting management systems and process discipline as critical factors influencing therapeutic success. As an implication, the formalization of SOPs and the integration of predictive tools like AI become crucial mandates for hospital management to ensure patient safety while maintaining institutional financial sustainability and ESG accountability.